Preparation and characterization of domperidone nanoparticles for dissolution improvement - Mohammed Sabar Al-lami; Malath H. Oudah; Firas A. Rahi (College of Pharmacy University of Baghdad, 2018)
This study was carried out to prepare and characterize domperidone nanoparticles to enhance solubility and the release rate. Domperidone is practically insoluble in water and has low and an erratic bioavailability range from 13%-17%. The domperidone nanoparticles were prepared by solvent/antisolvent precipitation method at different polymer:drug ratios of 1:1 and 2:1 using different polymers and grades of poly vinyl pyrolidone, hydroxy propyl methyl cellulose and sodium carboxymethyl cellulose as stabilizers. The effect of polymer type, ratio of polymer:drug, solvent:antisolvent ratio, stirring rate and stirring time on the particle size, were investigated and found to have a significant (p? 0.05) effect on particle size. The best formula was obtained with lowest average particle size of 84.05. This formula was studied for compatibility by FTIR and DSC, surface morphology by FESEM and crystalline state by XRPD. Then domperidone nanoparticles were formulated into a simple capsule dosage form in order to study of the in vitro release of drug from nanoparticles in comparison raw drug and mixture of polymer:drug ratios of 2:1. The release of domperidone from best formula was highly improved with a significant (p? 0.05) increase.